Hubungan Antara Kelekatan Emosional Guru dengan Perkembangan Kesehatan Mental Anak Tunagrahita - Adolfina Oualeng; Henderina Oualeng; Devi Natalia Berepalay (Departement of Mathematics Education, 2023)
Mental health development is needed by every individual, but not everyone has the multi-skills to develop like mentally retarded children. The aim of this research is to find out whether there is a relationship between teachers' emotional attachment and the development of children's mental health. The method used is a qualitative descriptive approach with data collection techniques using interviews. The results of the research show that there is a relationship between the teacher's emotional attachment and the Mental Health Development of State Special School Children with Mental Health C. Mental Health Development can occur because of the teacher's emotional attachment which is shown by the teacher's personality, teacher acceptance, teacher's self-demeanor, closeness in building verbal communication, gentleness , authoritative, disciplined, responsible, accepting of strengths and weaknesses, full of attention and affection and educating wholeheartedly.